The influence of liberalization in container haulage industry towards its safety performance / Nadia Othman - Othman, Nadia (Malaysia Institute of Transport, 2015)
This study was undertaken to identify the main cause of accidents involving container haulage and to determine the impacts of liberalization with regards to safety issues. After almost 10 years of liberalization, some operators think that authorities should consider stopping the issuance of new haulage licenses or giving new licenses only to existing companies to expand their fleet if the need arises. Many haulage operators hope to run their vehicle fleet profitably with a maximum return on the capital invested and at the same time prolonged the cycle of investment period. However, constraints such as budget limitations and increasing competition and challenges may possibly detract them from maintaining a safe fleet. In addition, reviews of well established literatures have been carried out as well as questionnaires have been distributed to assess the factors which contribute to accident - human factors and vehicle factors and how they are related to the impact of liberalization. Results of this survey were used to improve safety in container haulage industry by analyzing participants’ response through provided questions. The target population of this study comprises low, middle and top management who works in haulage companies and the sample size in this study is 107. Two types of software have been used in this study, namely Statistical Package for Social Sciences (SPSS) version 2.0 to key in the data and Analysis of Moment Structures (AMOS) version 2.0 to test the Structural Equation Modeling (SEM). By having this study, it is strongly believed that the container haulage industry in our country would get the significant impacts where results from this study help all related stakeholders to take immediate action to improve the safety aspects in overall operations. Apart from that, the hauliers can look forward into factors which are considered as important to their customers as to boost efficiency and to ensure the continually success of operations and business. The final finding shows that human factors have significant relationship to the impact of liberalization; therefore, authorities should take action and plan for improvement of human development among who are involved in the haulage industry. Moreover, by establishing an institution to develop a career path for the drivers can educate them and create a Malaysian driver as a 5- star driver.